Mountain national parks and ecological tourism - U. P. Suprunenko (Юг России: экология, развитие)
Eco-tourism is actively developed in high lands up to nival-glacial zone. Recreational resources are the object of eco-tourism, and, first of all, in national parks (zones: intensive and extensive recreation, buffer and difficult-to-access one), but every park has a specific profile, its own “ecorecreational face” and eco-touristic component. They can be used as a characteristic of park classification, as well as a terrain morphostructure. In general, the effective development in mountains requires to take into account eco-touristical features.